Quality assurance in RT-PCR-based BCR/ABL diagnostics - results of an interlaboratory test and a standardization approach - Burmeister, Thomas; Maurer, J.; Aivado, M.; Elmaagacli, A. H.; Grünebach, F.; Held, K. R.; Heß, G.; Hochhaus, Andreas; Höppner, W.; Lentes, K. U.; Lübbert, M.; Schäfer, K. L.; et al. (Leukemia, 2000)
Here we describe the results of an interlaboratory test for RT-PCR-based BCR/ABL analysis. The test was organized in two parts. The number of participating laboratories in the first and second part was 27 and 20, respectively. In the first part samples containing various concentrations of plasmids with the ela2, b2a2 or b3a2 BCR/ABL transcripts were analyzed by PCR. In the second part of the test, cell samples containing various concentrations of BCR/ABL-positive cells were analyzed by RT-PCR. Overall PCR sensitivity was sufficient in approximately 90% of the tests, but a significant number of false positive results were obtained. There were significant differences in sensitivity in the cell-based analysis between the various participants. The results are discussed, and proposals are made regarding the choice of primers, controls, conditions for RNA extraction and reverse transcription.